Use of Bio-fertilizer and its Effect on Seedling’s Growth - Barua, R. S. (Indian Forester, 1994)
Acacia nilotica (Linn) Willd, ex del, variety Cupressiformis is a common species grown in Northern and Central India. The species has potential if used in agro-forestry applications because of the crown diameter being smaller than Acacia nilotica variety jacquemontii. Application of Rhizobium was tried in the nursery to see its effect on the growth of seedlings. 125 g of Rhizobium was in mixed with 1 kg of the seeds, in a slurry, dried and sown in mother beds showed the best results in height growth of the seedlings, when used in bags of size:16x30 cm.